The concept of education according to Ibn Khaldun and its implementation in children’s education in Kuttab Permata Qur’an Kartasura - Solikhah, Putri Irma; Purnomo, Purnomo (TARBAWY: Indonesian Journal of Islamic Education, 2023)
Ibn Khaldun’s thoughts can be used to criticize Islamic educational institutions, which tend not to emphasize independent thinking and broaden the subject of study. Only a little development can be expected from established educational institutions such as schools, madrasas, and Islamic boarding schools (Pesantren). Kuttab, as a reborn classical educational institution, has the potential to implement Ibn Khaldun’s educational thinking more flexibly because it does not yet have a standardized learning system. This research is qualitative field research in Kuttab Permata Qur’an. Data related to the implementation of learning in Kuttab Permata Qur’an is examined from the perspective of Ibn Khaldun’s educational concept with a phenomenological approach. The results of this study indicate that education at Kuttab Permata Qur’an is compatible with Ibn Khaldun’s thought in curriculum aspects relevant to the needs of life in society and dignified relations between teachers and students. However, teachers still need to demonstrate a convincing ability to simplify concepts in learning materials.Pemikiran Ibn Khaldun dapat digunakan untuk mengkritisi lembaga pendidikan Islam yang cenderung tidak menekankan pemikiran independen dan memperluas subjek kajian. Hanya sedikit perkembangan yang bisa diharapkan dari lembaga pendidikan yang sudah mapan seperti sekolah, madrasah, dan pesantren (Pesantren). Kuttab sebagai lembaga pendidikan klasik yang terlahir kembali berpotensi mengimplementasikan pemikiran pendidikan Ibn Khaldun secara lebih fleksibel karena belum memiliki sistem pembelajaran yang terstandar. Penelitian ini merupakan penelitian lapangan kualitatif dalam Kuttab Permata Qur’an. Data terkait pelaksanaan pembelajaran dalam Kuttab Permata Qur’an dikaji dari sudut pandang konsep pendidikan Ibn Khaldun dengan pendekatan fenomenologis. Hasil penelitian ini menunjukkan bahwa pendidikan di Kuttab Permata Qur’an sesuai dengan pemikiran Ibn Khaldun dalam aspek kurikulum yang relevan dengan kebutuhan hidup masyarakat dan hubungan bermartabat antara guru dan siswa. Namun, guru tetap perlu menunjukkan kemampuan meyakinkan dalam menyederhanakan konsep dalam materi pembelajaran.